Type A Behaviours and Heart Disease: Epidemiological and Experimental Foundations - Paul Bennett; Douglas Carroll (Behavioural Neurology)
This paper critically examines three strands of evidence that concern the relationship between type A behaviours and coronary heart disease; prospective epidemiological studies of healthy populations, studies of those at high risk for coronary heart disease, and angiographic studies of atherosclerosis. The first of these would seem to provide the strongest test. Methodological and conceptual issues mean that the results of studies using the other methods should be interpreted with care. It is concluded that there is relatively strong evidence of an association between Type A behaviour as measured by Structured Interview and coronary heart disease. Hostility and anger appear to be the most powerful determinants of CHD. However, it is likely that they interact with other type A behaviours and related environmental factors in determining risk.